Ruthenium-copper bimetal active phase nanosheet catalyst, preparation method and application in removal of volatile pollutants

By loading a ruthenium-copper bimetallic component on a titanium dioxide nanosheet carrier, a ruthenium-copper bimetallic active phase nanosheet catalyst is prepared, which solves the problems of high cost, low stability and poor water resistance of existing catalysts, and achieves high efficiency. , Stable removal of acetone.

CN119318970APending Publication Date: 2025-01-17XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411424704.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing catalysts are costly and have low stability when removing the oxygen-containing volatile organic compound acetone, and have poor treatment effects when facing a mixture of acetone and water vapor.

Method used

The ruthenium-copper bimetallic active phase nanosheet catalyst is prepared by hydrothermal method and impregnation method. Titanium dioxide nanosheets are used as carriers and the ruthenium-copper bimetallic component is loaded as the active center to achieve synergistic catalysis.

Benefits of technology

It significantly improves the low-temperature catalytic efficiency and stability of the catalytic material. It can convert 90% of acetone at 140°C and completely mineralize acetone at 200°C. It has good water resistance and low energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318970A_ABST
    Figure CN119318970A_ABST
Patent Text Reader

Abstract

The invention discloses a ruthenium-copper bimetal active phase nanosheet catalyst, a preparation method and application of the ruthenium-copper bimetal active phase nanosheet catalyst in removal of volatile pollutants, and belongs to the technical field of catalytic purification of volatile organic compounds. The ruthenium-copper bimetallic active phase nanosheet catalyst is prepared through a hydrothermal method and an impregnation method, a two-dimensional material titanium dioxide nanosheet serves as a carrier, a ruthenium-copper bimetallic component is loaded on the surface of the two-dimensional material titanium dioxide nanosheet to serve as an active center, and through the synergistic catalysis of the ruthenium-copper bimetallic active phase, the performance limitation of a single metal component is broken through; compared with a ruthenium / copper catalyst with a single metal active phase, the bimetallic active phase greatly improves the low-temperature catalytic efficiency and stability of a catalytic material, the preparation method is simple, the cost is relatively low, and the improvement of activity and stability is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic purification of volatile organic compounds, and specifically relates to a nanosheet catalyst with a bimetallic active phase, a preparation method and an application of the catalyst in removing acetone, a typical oxygen-containing volatile organic pollutant. Background Art

[0002] Volatile Organic Compounds (VOCs) refer to organic compounds with a saturated vapor pressure greater than 70.91 Pa at room temperature and a boiling point less than 260°C at normal pressure. Among all VOCs, oxygenated VOCs (OVOCs) are more likely to form ozone than other VOCs. Among them, acetone containing C=O, CC and CH bonds is the most typical and one of the most abundant OVOCs in the atmosphere. As a common solvent or intermediate, acetone is widely used in plastics, rubber, fiber, medicine, pharmaceuticals, packaging and printing industries. Acetone not only causes water pollution, but also has an anesthetic effect on the human central nervous system and damages the kidneys and pancreas. Therefore, controlling the release of acetone and effectively removing acetone from the environment is of great significance to protecting the environment.

[0003] Catalytic oxidation technology has been widely used in industrial VOC emission reduction due to its advantages such as high removal efficiency and low operating temperature. In recent years, precious metal-based catalysts have been often used in the catalytic oxidation of OVOCs such as acetone. The good activity of precious metals and catalysts has greatly reduced the reaction temperature of complete oxidation of acetone and increased the mineralization rate. However, single precious metal-based catalysts are expensive and have low stability, and their catalytic activity is easily affected by other components in the reaction gas. Single transition metal copper oxides have good stability, but their activity is usually lower than that of precious metal-based materials. In actual industrial emissions, acetone usually coexists with water vapor. When most single precious metal and transition metal-based catalysts are faced with a mixture of acetone and water vapor, the treatment effect will be significantly affected due to the toxic effect of water vapor.

[0004] Therefore, there is an urgent need to develop a catalyst that is suitable for actual working conditions, has excellent catalytic performance, good water resistance and low price. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a ruthenium-copper bimetallic active phase nanosheet catalyst and a preparation method and application of removing volatile pollutants, so as to solve the problem that the existing catalysts cannot meet the requirements of good catalytic performance and stability while effectively controlling production costs.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a ruthenium-copper bimetallic active phase nanosheet catalyst, comprising the following steps: 1) Add copper salt or copper salt solution into water, then add polyvinyl pyrrolidone (PVP) as a protective agent, stir well to obtain a suspension; 2) adding a certain amount of ruthenium salt or ruthenium salt solution to the suspension and stirring the mixture to obtain a mixed system; 3) Add the carrier titanium dioxide nanosheets to the mixed system, stir evenly at room temperature, then continue to add the freshly prepared sodium borohydride solution and stir thoroughly, centrifuge to separate the product and wash; 4) The product obtained in step 3) is calcined at 300-400°C for 1-3 hours, and then reduction calcined at 200-400°C for 2-4 hours to obtain a ruthenium-copper bimetallic active phase nanosheet catalyst Ru-Cu / TiO2.

[0007] Preferably, the copper salt accounts for 0.5 wt%-10 wt% of the mass of the carrier titanium dioxide nanosheets; the mass ratio of the added polyvinyl pyrrolidone to the copper salt is 0.5-20:1; and the ruthenium salt or ruthenium salt solution is added to the suspension at a molar ratio of Ru:Cu of 0.5-20:1.

[0008] Preferably, the copper salt is copper nitrate, copper sulfate or copper chloride, and the ruthenium salt is ruthenium trichloride.

[0009] Preferably, in step 4), the calcination treatment is carried out from room temperature to 300-400° C. at a heating rate of 1-5° C. / min.

[0010] Preferably, in step 4), the reduction roasting treatment is carried out from room temperature to 200-400°C at a heating rate of 1-5°C / min, and the carrier gas during the reduction roasting treatment is a mixture of hydrogen and argon, with hydrogen accounting for 5%-10% of the volume of the mixture, and the air intake flow rate is 50-200 mL / min.

[0011] Preferably, the carrier titanium dioxide nanosheets are prepared by the following method: Titanium tetrachloride is added to ethylene glycol and stirred at room temperature. Deionized water is then added to the reaction system to obtain a mixed solution. The mixed solution is heated at 150°C for 4-8 hours and then cooled to room temperature, centrifuged, washed, and dried, and then calcined at 300-400°C for 2-4 hours to obtain carrier titanium dioxide nanosheets.

[0012] The present invention also discloses a ruthenium-copper bimetallic active phase nanosheet catalyst prepared by the above preparation method, wherein the specific surface area of ​​the catalyst is 80-100 m2 / g.

[0013] The invention also discloses the application of the ruthenium-copper bimetallic active phase nanosheet catalyst for removing volatile pollutants.

[0014] Preferably, the catalyst is used for low temperature purification of volatile oxygenated hydrocarbons.

[0015] Further preferably, the catalyst can achieve a conversion rate of 90% at a concentration of 500 ppm of acetone at 140°C and remain active within 24 hours; The catalyst can completely mineralize acetone with a concentration of 500 ppm at 200°C.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention prepares ruthenium-copper bimetallic active phase nanosheet catalysts by hydrothermal method and impregnation method. The core invention point is to use two-dimensional material titanium dioxide nanosheet as a carrier, load ruthenium-copper bimetallic components on its surface as active centers, and break through the performance limitation of a single metal component through the synergistic catalytic effect of the ruthenium-copper bimetallic active phase. Compared with the ruthenium / copper catalyst of a single metal active phase, the bimetallic active phase prepared by the present invention greatly improves the low-temperature catalytic efficiency and stability of the catalytic material. The preparation method is simple, relatively low-cost, and achieves improved activity and stability.

[0017] The ruthenium-copper bimetallic active phase nanosheet catalyst prepared by the above method of the present invention can be used in the purification of volatile oxygen-containing hydrocarbons. The catalyst has low energy consumption when used, can convert 90% of acetone with a concentration of 500 ppm at low temperature (140°C), and can completely mineralize acetone with a concentration of 500 ppm at a relatively low temperature (200°C). Experiments have confirmed that the catalyst has good stability and anti-poisoning ability. The catalyst degraded 500 ppm acetone at 140°C for 24 hours without deactivation, showing good stability; the catalyst can maintain the ability to degrade 500 ppm acetone at 140°C and under various water content conditions, showing good water resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 These are transmission electron microscopy characterization pictures such as EDS-Mapping of the ruthenium-copper bimetallic active phase nanosheet catalyst prepared in Example 4 of the present invention, wherein (a) is a high-magnification transmission electron microscopy image of the ruthenium-copper bimetallic nanosheet catalyst at 50 nm, (b) is a 5 nm HAADF image of the ruthenium-copper bimetallic nanosheet catalyst, (c) is a surface scanning image of the Ru element, and (d) is a surface scanning image of the Cu element.

[0019] Figure 2This is the XRD characterization diagram of the ruthenium-copper bimetallic active phase nanosheet catalyst prepared in Example 4 of the present invention.

[0020] Figure 3 This is a comparison chart of the activities of the ruthenium-copper bimetallic active phase nanosheet catalyst prepared in Example 4 of the present invention, the copper-based nanosheet catalyst prepared in Example 3 of the present invention, the ruthenium-based nanosheet catalyst prepared in Example 2 of the present invention, and the titanium dioxide nanosheet carrier prepared in Example 1 of the present invention for catalytic oxidation of acetone. Figure 4 This is a graph showing the stability experimental results of the ruthenium-copper bimetallic active phase nanosheet catalyst prepared in Example 4 of the present invention for catalytic oxidation of acetone under 24h conditions.

[0021] Figure 5 This is a test chart of the water resistance stability of the ruthenium-copper bimetallic active phase nanosheet catalyst prepared in Example 4 of the present invention for catalytic oxidation of acetone under different humidity conditions. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0023] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0024] The present invention is further described in detail below in conjunction with the accompanying drawings: Example 1: Preparation of titanium dioxide carrier with nanosheet morphology 2 mL of titanium tetrachloride was added to 70 mL of ethylene glycol and stirred at room temperature until no more hydrogen chloride gas was produced in the reaction, and then 2 mL of water was added to the reaction system. The homogeneous light yellow solution was transferred to a high-pressure reactor and heated at 150 ° C for 4 hours. After the reactor was cooled to room temperature, the suspension after the reaction was taken out and centrifuged at high speed to obtain a white precipitate. The obtained white precipitate was washed three times with deionized water and ethanol and then centrifuged. Finally, the centrifuged sample was placed in an oven at 80 ° C and dried for 12 hours. The dried solid was transferred to a crucible and calcined at 350 ° C for 4 hours. The calcination process was carried out in air and finally cooled to room temperature to obtain a titanium dioxide nanosheet carrier.

[0025] Example 2: Preparation of a single ruthenium-based catalyst 0.05-0.07 g PVP was added to 30 mL ultrapure water. After sufficient stirring, 5 mL of ruthenium trichloride precursor solution (concentration of 0.01 mol / L) was added to the solution, and then stirred at room temperature for 20 minutes to obtain a dark brown solution. After sufficient stirring, 0.5 g of titanium dioxide nanosheets synthesized in Example 1 was added to the solution, and then the suspension was stirred at room temperature for 20 minutes. 40 mL of 0.1 mol / L sodium borohydride solution was added dropwise to the suspension, and then the suspension was stirred at room temperature for 30 minutes. After centrifugation of the product, the centrifuged sample was placed in an oven at 80 ° C and dried for 12 hours. The sample was then calcined at 350 ° C for 2 hours. Finally, the sample was placed in a porcelain boat and reduced at 200 ° C for 2 hours in a mixed atmosphere of H2 and Ar (H2 accounts for 10% of the volume of the mixed gas) to obtain a pristine ruthenium-based nanosheet catalyst (Ru / TiO2) with a ruthenium loading of 1wt%; Example 3: Preparation of a single copper-based catalyst 1 mL of copper nitrate mother solution (0.1 mol / L) was added to 24 mL of ultrapure water, 0.05-0.07 g of PVP was added to the clear solution, and then the suspension was stirred at room temperature for 20 minutes. 0.5 g of titanium dioxide nanosheets synthesized in Example 1 were added to the solution, and then the suspension was stirred at room temperature for 20 minutes. 40 mL of 0.1 mol / L sodium borohydride solution was added dropwise to the suspension, and then the suspension was stirred at room temperature for 30 minutes. The product was separated by centrifugation at 8000 r / min for 10 minutes and further washed with deionized water. After being heated to 350 ℃ in air in a muffle furnace, it was kept at 350 ℃ for calcination for 2h (heating rate of 2 ℃ / min). Finally, the sample was placed in a porcelain boat and reduced at 200 ℃ for 2 hours in a mixed atmosphere of H2 and Ar (H2 accounts for 10% of the volume of the mixed gas) to obtain a copper-based nanosheet catalyst (Cu / TiO2) with a copper loading of 1 wt%; Example 4: Preparation of a bimetallic active phase catalyst with a ruthenium-copper molar ratio of 1:2 1 mL of copper nitrate mother solution (0.1 mol / L) was added to 24 mL of ultrapure water, 0.05-0.07 g of PVP was added to the clear solution, and after sufficient stirring, 5 mL of ruthenium trichloride precursor solution (concentration of 1.0107 mg Ru / mL) was added to the suspension, and then the suspension was stirred at room temperature for 20 minutes to obtain a dark black solution. After sufficient stirring, 0.5 g of titanium dioxide nanosheets synthesized in Example 1 was added to the solution, and then the suspension was stirred at room temperature for 20 minutes. 40 mL of 0.1 mol / L sodium borohydride solution was added dropwise to the suspension, and then the suspension was stirred at room temperature for 30 minutes. The product was separated by centrifugation at 8000 r / min for 10 minutes and further washed with deionized water. After being heated to 350 °C in air in a muffle furnace, it was kept at 350 °C for calcination for 2h (heating rate of 2 °C / min). Finally, the sample was placed in a porcelain boat and reduced at 200 °C for 2 hours in a mixed atmosphere of H2 and Ar (H2 accounted for 5% of the mixed gas volume) to obtain a ruthenium-copper bimetallic nanosheet catalyst (Ru-Cu / TiO2) with a ruthenium-copper molar ratio of 1:2 (the ruthenium and copper loadings were both 1wt%). TEM and HRTEM characterization of Ru-Cu bimetallic nanosheets Figure 1 ,from Figure 1 In (a), it can be seen that the catalysts prepared in steps 1-4 have a morphology of nanosheets with a size of about tens of nanometers. Figure 1 As can be seen in Figure (b), the active component particles are evenly distributed on the crystal surface of the catalyst support. Figure 1 As shown in (c) and (d), EDS analysis shows that the active component particles are composed of Ru and Cu with relatively uniform distribution, which fully demonstrates the formation of dual active phases in the synthetic material. The uniform distribution of active components on the support surface is conducive to the decomposition of volatile organic pollutants by the catalyst. The X-ray diffraction pattern of the ruthenium-copper bimetallic nanosheet catalyst is shown in Figure 2 The results showed that only the titanium dioxide diffraction peak existed, specifically a mixture of TiO2-B phase and anatase phase. No diffraction peaks related to Ru and Cu were found in the XRD graph, which also indirectly verified the uniform distribution of Ru and Cu on the surface of the titanium dioxide nanosheet carrier.

[0026] Example 5: Activity experiment of catalytic decomposition of acetone by different catalysts The catalytic reaction is carried out in a VOC reaction device. The catalyst prepared by the methods in Example 1, Example 2, Example 3, and Example 4 is pressed into tablets and sieved (40-60 mesh), 0.2 g of the sieved catalytic material is weighed, activated at 40°C for 2 h, and a catalytic oxidation experiment is carried out on acetone. The reaction conditions are: total flow rate 200 mL / min, acetone concentration 500 ppm, N2 as a balance gas, oxygen volume concentration 21%, and the catalytic reaction activity of the catalyst at 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C, 260°C, 280°C, and 300°C is tested respectively. The reaction products are monitored and analyzed by gas chromatography and online mass spectrometry, and sampling is performed every 2 min using an automatic sampler; Acetone conversion rate (%) = (Ace in -Ace out ) / Ace in ×100, of which Ace in Represents the inlet acetone concentration, Ace out represents the outlet acetone concentration; Activity test results such as Figure 3 As shown, Figure 3 The data show that the conversion rate of ruthenium-copper bimetallic nanosheet catalyst increases with the increase of temperature. At 140 °C, 90% of acetone can be converted (i.e., 140 °C reaches T 90 ), at 200 °C, the ruthenium-copper bimetallic nanosheet catalyst synthesized in Example 4 can completely convert acetone, and its activity is significantly higher than that of the ruthenium-based nanosheet catalyst synthesized in Example 2, the copper-based nanosheet catalyst synthesized in Example 3, and the titanium dioxide nanosheet carrier synthesized in Example 1.

[0027] Example 6: Stability test of catalytic decomposition of acetone by ruthenium-copper bimetallic active phase catalyst At 140°C (T 90 ) conditions, the stability test of the ruthenium-copper bimetallic active phase catalyst synthesized in Example 4 for the catalytic decomposition of acetone was carried out, and the other conditions were consistent with the activity test experiment.

[0028] The stability test results are shown in Figure 4 , the ruthenium-copper catalyst still showed a conversion rate of more than 90% after the reaction for 24 h. It can be seen from the activity experiment and the stability experiment that the ruthenium-copper catalyst synthesized in Example 4 has good stability in catalyzing the degradation of acetone, and has certain practical application potential.

[0029] Example 7: Water resistance experiment of ruthenium-copper bimetallic active phase catalyst for catalytic decomposition of acetone at different humidity At 140°C (T 90 ) conditions, the water resistance test of the ruthenium-copper bimetallic active phase catalyst synthesized in Example 4 for catalytic decomposition of acetone was carried out, except that the water content in the reaction was controlled to 1% and 3%, and the other conditions were consistent with the activity test experiment.

[0030] The results of catalytic decomposition of acetone by Ru-Cu bimetallic active phase catalyst at different humidity are as follows Figure 5 As shown. At 140 ° C, due to the competitive adsorption of water and acetone molecules on the active sites of the catalyst, the conversion rate of the catalyst to acetone decreased slightly. The conversion rate of the catalyst to acetone was about 85% under the condition of 1% water content, and the conversion rate of the catalyst to acetone was still more than 80% under the condition of 3% water content. After the presence of water in the mixed gas was cut off, the conversion rate of the catalyst to acetone returned to the initial level. The above results show that the ruthenium-copper bimetallic active phase catalyst synthesized in Example 4 has excellent water resistance, can maintain good activity for the catalytic oxidation of acetone under various humidity conditions, and has certain practical application potential.

[0031] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a ruthenium-copper bimetallic active phase nanosheet catalyst, characterized in that: The following steps are involved: 1) Add copper salt or copper salt solution into water, then add polyvinyl pyrrolidone, stir well to obtain a suspension; 2) adding ruthenium salt or ruthenium salt solution to the suspension and stirring well to obtain a mixed system; 3) Add the carrier titanium dioxide nanosheets to the mixed system, stir evenly at room temperature, then continue to add sodium borohydride solution and stir well, centrifuge and separate the product and wash; 4) The product obtained in step 3) is calcined at 300-400°C for 1-3 hours, and then reduction calcined at 200-400°C for 2-4 hours to obtain a ruthenium-copper bimetallic active phase nanosheet catalyst Ru-Cu / TiO2.

2. The method for preparing the ruthenium-copper bimetallic active phase nanosheet catalyst according to claim 1, characterized in that: The amount of copper salt added is 0.5wt%-10wt% of the mass of the carrier titanium dioxide nanosheet; the mass ratio of the added polyvinyl pyrrolidone to the copper salt is 0.5-20:1; and ruthenium salt or ruthenium salt solution is added to the suspension according to a molar ratio of Ru:Cu of 0.5-20:

1.

3. The method for preparing the ruthenium-copper bimetallic active phase nanosheet catalyst according to claim 1, characterized in that: The copper salt is copper nitrate, copper sulfate or copper chloride, and the ruthenium salt is ruthenium trichloride.

4. The method for preparing the ruthenium-copper bimetallic active phase nanosheet catalyst according to claim 1, characterized in that: In step 4), the calcination treatment is carried out by heating the temperature from room temperature to 300-400° C. at a heating rate of 1-5° C. / min.

5. The method for preparing the ruthenium-copper bimetallic active phase nanosheet catalyst according to claim 1, characterized in that: In step 4), the reduction roasting treatment is carried out from room temperature to 200-400°C at a heating rate of 1-5°C / min. During the reduction roasting treatment, the carrier gas is a mixture of hydrogen and argon, and the hydrogen accounts for 5%-10% of the volume of the mixture. The air intake flow rate is 50-200 mL / min.

6. The method for preparing the ruthenium-copper bimetallic active phase nanosheet catalyst according to any one of claims 1 to 5, characterized in that: The carrier titanium dioxide nanosheet is prepared by the following method: Titanium tetrachloride is added to ethylene glycol and stirred at room temperature. Deionized water is then added to the reaction system to obtain a mixed solution. The mixed solution is heated at 150°C for 4-8 hours and then cooled to room temperature, centrifuged, washed, and dried, and then calcined at 300-400°C for 2-4 hours to obtain carrier titanium dioxide nanosheets.

7. A ruthenium-copper bimetallic active phase nanosheet catalyst prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The specific surface area of ​​the catalyst is 80-100 m 2 / g.

8. The ruthenium-copper bimetallic active phase nanosheet catalyst according to claim 7 is used to remove volatile pollutants.

9. The use according to claim 8, characterized in that The catalyst is used for low-temperature purification of volatile oxygen-containing hydrocarbons.

10. The use according to claim 9, characterized in that The catalyst can achieve a 90% conversion rate of 500 ppm acetone at 140°C and remain active for 24 hours. The catalyst can completely mineralize acetone with a concentration of 500 ppm at 200°C.